Divided Cities : Partition and Its Aftermath in Lahore and Amritsar, 1947-1957 - Series Editor Talbot, Ian (Karachi Oxford University Press, 2006)
Talbot studies the impact of the 1947 partition of the Punjabi cities of Lahore and Amritsar, providing important comparative insights into the processes of violence, demographic transformation, and physical reconstruction.
Include, Index, Notes, Bibligraphy and Illustrations.
Keywords: Pakistan -- Amritsar (India) -- History. -- India -- History -- Partition, 1947